2012
DOI: 10.1590/s0004-282x2012000700004
|View full text |Cite
|
Sign up to set email alerts
|

Objective and subjective analysis of women's voice with idiopathic Parkinson's disease

Abstract: OBJECTIVE: To compare the voice quality of women with idiopathic Parkinson's disease and those without it. METHODS: An evaluation was performed including 19 female patients diagnosed with idiopathic Parkinson's disease, with an average age of 66 years, and 27 women with an average of 67 years-old in the Control Group. The assessment was performed by computed acoustic analysis and perceptual evaluation. RESULTS: Parkinson's disease patients presented moderate rough and unstable voice quality. The parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Five controlled studies evaluated perceptual voice quality between patients with IPD and controls using the GRBASI scale . The observations varied between studies even though the overall trend showed stronger scores in dysphonia, breathiness, roughness and instability in patients with IPD.…”
Section: Discussionmentioning
confidence: 99%
“…Five controlled studies evaluated perceptual voice quality between patients with IPD and controls using the GRBASI scale . The observations varied between studies even though the overall trend showed stronger scores in dysphonia, breathiness, roughness and instability in patients with IPD.…”
Section: Discussionmentioning
confidence: 99%